Contrast‐enhanced optical coherence tomography for melanoma detection: An in vitro study. Issue 5 (26th February 2020) - Jalilian, Elmira; Xu, Qiuyun; Horton, Luke; Fotouhi, Audrey; Reddy, Shriya; Manwar, Rayyan; Daveluy, Steven; Mehregan, Darius; Gelovani, Juri; Avanaki, Kamran
Abstract: Optical coherence tomography (OCT), with a high‐spatial resolution (<10 microns), intermediate penetration depth ( 1.5 mm) and volumetric imaging capability is a great candidate to be used as a diagnostic‐assistant modality in dermatology. At this time, the accuracy of OCT for melanoma detection is lower than anticipated. In this letter, we studied for the first time, the use of a novel contrast agent consist of ultra‐small nanoparticles conjugated to a melanoma biomarker to improve the accuracy of OCT for differentiation of melanoma cells from nonmelanoma cells, in vitro. We call this approach SMall nanoparticle Aggregation‐enhanced Radiomics of Tumor (SMART)‐OCT imaging. This initial proof of concept study is the first step toward the broad utilization of this method for high accuracy all types of tumor detection applications. Abstract : At this time, the accuracy of optical coherence tomography (OCT) for melanoma detection is lower than anticipated. In this letter, we studied for the first time, the use of a novel contrast agent consist of ultra‐small nanoparticles conjugated to a melanoma biomarker to improve the accuracy of OCT for differentiation of melanoma cells from non‐melanoma cells, in vitro. We call this approach Small nanoparticle Aggregation‐enhanced Radiomics of Tumor (SMART)‐OCT imaging.